Efektivitas Sosialisasi Bahaya Narkotika Pada Mahasiswa Oleh Dinas Pemuda Dan Olahraga Provinsi Sumatera Selatan - Iriani, Atrika; Maria, Kiki (@-Publik: Jurnal Administrasi Publik, 2021)
This study aims to determine and analyze the Effectiveness of Socialization of Narcotics Hazards to Students by the Youth and Sports Office of South Sumatra Province. This research is a descriptive research with a qualitative approach. The data used is based on the type of quantitative data and qualitative data while based on the source is primary data and secondary data. The data collection instruments used were observation, interviews and documentation. The informants in this study were the Secretary of the Department of Youth and Sports of South Sumatra Province; Head of Sub-Division of Planning, Evaluation and Reporting of the Youth and Sports Office of South Sumatra Province; Head of Youth Empowerment Division of Youth and Sports Office of South Sumatra Province; Head of Prevention and Community Empowerment of the National Narcotics Agency of South Sumatra Province; Student participants in the socialization of the dangers of drugs as a cross check. Data analysis is a qualitative analysis with an interactive model. Based on the results of the research, it is known that the implementation of the Socialization of Narcotics Hazards to Students by the Youth and Sports Office of the Province of South Sumatra is quite effective although it needs to be increased again because the number of competent human resources / officers as resource persons / extension workers in socialization activities and budget resources are still limited.